IMPLEMENTASI PEMBELAJARAN ETNOSAINS (ADAT SASI) PADA MATERI EKOSISTEM KELAS V BERBASIS ARTICULATE STORYLINE 3 DI SEKOLAH DASAR - Raizha, Ruth; Yektiningtyas, Wigati; Indah Slamet Budiarti; Kusdianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of integration of local wisdom in science learning in elementary schools, especially in ecosystem material for grade V within the Merdeka Curriculum framework. The Sasi tradition as a form of ethnoscience of the Nabire community has great potential to be integrated into the learning process oriented towards the Pancasila Student Profile. However, the low utilization of interactive learning media and the limited connection between local science and formal science material are obstacles that need to be overcome. This study aims to describe the implementation of ethnoscience learning based on the Sasi tradition in ecosystem material for grade V developed through the Articulate Storyline 3 media in elementary schools. The type of research used is qualitative research with a descriptive approach. The research subjects included the principal, grade V teachers, and grade V students of SD Negeri Inpres 01 Sanoba, Nabire Regency, Central Papua Province. Data collection techniques included observation, in-depth interviews, and documentation, with data validity using source triangulation. The results of the study indicate that the implementation of Sasi-based ethnoscience learning through Articulate Storyline 3 media can increase students' learning motivation, strengthen the understanding of ecosystem concepts contextually, and introduce local wisdom values ​​that are aligned with the dimensions of the Pancasila Student Profile. Obstacles found include limited teacher technological competence and media preparation time. The solutions implemented include peer-based technology training and gradual media development. This study concludes that the integration of Sasi indigenous ethnoscience and Articulate Storyline 3 media in ecosystem science learning provides a meaningful, contextual, and enjoyable learning experience for fifth-grade elementary school students. Keywords : Ethnoscience, Sasi, Science, Ecosystem, Articulate Storyline 3